Adolescents' experiences and perceptions of dementia. (2nd July 2020) - Farina, Nicolas; Hughes, Laura J.; Griffiths, Alys W.; Parveen, Sahdia
Abstract: Objectives: There is a lack of understanding about how adolescents perceive dementia, and what their dementia related experiences are. Without such information, it is hard to make a case for the need to raise awareness of dementia in adolescents, and the best strategies to achieve this. Methods: In a cohort of 901 adolescents (aged 13–18) from the South East of England, we explored what the experiences and perceptions of dementia were using a series of questionnaires. Descriptive data of individual items were reported, comparing differences between genders. Results: The adolescents within this study tended to have positive or neutral attitudes towards dementia, though there was evidence that a proportion of adolescents had misconceptions or held negative attitudes (e.g. 28.5% of adolescents disagreed with the statement 'In general, I have positive attitudes about people with dementia'). We also identified that the adolescents had a range of experiences of dementia including providing some form of care for someone with dementia (23.2%), though most had indirect contact with dementia through TV and movies (77.3%), or adverts (80.2%). Females nearly always had better attitudes towards dementia and had significantly more contact with dementia. Conclusions: Considering that adolescents are already forming negative attitudes and misconceptions of dementia, it is important that we raise awareness about dementia in this age group.